Correlation and difference of hamular distance and width of maxillary anterior teeth among UPCD students, 2009 - Jao, Caireen Gail N.; Lachica, Marie Rossini Carmela T.; Ramos, Tristan Nathaniel C.; Mendoza, Michael Antonio F. (Adviser).
In complete denture prosthodontics, selection of the most suitable maxillary anterior artificial teeth has much to do with the eventual success or failure of the service. Many attempts have been made to establish methods of estimating the width of the maxillary anterior teeth. The aim of this study is to determine if there's correlation between the measurements of the hamular distance and maxillary anterior teeth width as well as to determine if there is a significant difference between the two measurements among students of the University of the Philippines, College of Dentistry. Maxillary anterior teeth width and hamular distance were measured on casts of 43 subjects (34 female and 9 male). Pearson correlation coefficients were calculated to determine the relationship between the two variables. On the other hand, paired t-test was used as statistical method to determine if the two measurements are significantly different (a=0.05). Results have shown that all Pearson correlation coefficients for the female, male and combined population ( r = 0.11, 0.08 respectively) were small. No significant relationship existed between the hamular distance and maxillary anterior teeth width among the male and female population, taken separately and combined (p>0.05). Results have also shown that there is statistically significant difference between the two variables among females (p<0.05) but there is no statistically significant difference among males (p>0.05). For the combined male and female subjects, there is no statistically difference between the two variables (p<0.05). Conclusion of these study are: 1.) There is no correlation between the hamular distance and maxillary anterior teeth widths among the male, female and combined population. 2.) There is significant difference between the hamular distance and maxillary anterior teeth width among the female population. 3.) There is no significant difference between the two variables in the male and combined population. Within the limitations of this study, the results suggest that the biometric ratio that may be obtained to estimate the width of maxillary anterior teeth may be clinically applicable only to a portion of the population. Furthermore, as statistical significance may differ with clinical significance, mean difference for females (1.35mm) and males (-2.57) may be used clinically to help predict the width of the maxillary anteriors.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Prosthodontics; Hamular distance; Maxillary anterior teeth width